Oriental Medical Treatment of chronic Acalculous Cholecystitis - Hae-Yeon Lee; Jung-Han Park; Hyun-Seok Cho; Jung-Chul Kim; Tae-Hyun Baik; Jong-Seong Wi (Korean Pharmacopuncture Institute, 2004)
Chronic acalculous cholecystitis gets possession of about 12 to 13 percent of patients with chronic cholecystitis. Pathologically it is characterised by chronic inflammation and thickening of the gallbladder wall but doesn't come across stones. Clinical symptoms are vague and include abdominal discomfort and distension, nausea, flatulence and intolerance of fatty foods. A patient on chronic acalculous cholecystitis diagnosed from his clinical symtoms and abdominal ultrasonogram was treated by Geonbihwan, acupuncture and herbal acupuncture. Satisfactory symptomatic improvement was achieved and findings of abdominal ultrasonogram came also normal.